Purchase and redemption decisions of mutual fund investors and the role of fund families - Stephan Jank; Michael Wedow (Deutsche Bundesbank, 2010)
This paper investigates the purchases and redemptions of a large cross-sectional sample of German equity funds. We find that investors punish bad performance by selling their shares, but also have a tendency to sell winners. Investors in large fund families show higher sales and redemption rates. Furthermore, family size also affects the flow-performance relationship. On the one hand, investors in large families punish bad performance more, on the other, they also tend to sell winners more. Finally, we find that inner-family rankings play an important role for redemptions, with investors strongly redeeming their shares from intra-family losers.
Keywords: G20; G23; 330; Mutual funds; fund family; flow-performance relationship; Investmentfonds; Institutioneller Anleger; Anlageverhalten; Portfolio-Management; Aktienfonds; Wertpapieranalyse; Schätzung; Deutschland